In vivo knee kinematics of an innovative prosthesis design - Worlicek Michael; Schaumburger Jens; Springorum Robert; Maderbacher Guenther; Zeman Florian; Grifka Joachim; Baier Clemens (Open Medicine, 2022)
Up to 20% of patients after total knee arthroplasty (TKA) are not satisfied with the result. Several designs of new implants try to rebuild natural knee kinematics. We hypothesized that an innovative implant design leads to better results concerning femoral rollback compared to an established implant design. For this pilot study, 21 patients were examined during TKA, receiving either an innovative (ATTUNETM Knee System (DePuy Inc.), n = 10) or an established (PFCTM (DePuy Inc.), n = 11) knee system. All patients underwent computer navigation. Knee kinematics was assessed after implantation. Outcome measure was anterior–posterior translation between femur and tibia. We were able to demonstrate a significantly higher femoral rollback in the innovative implant group (p < 0.001). The mean rollback of the innovative system was 11.00 mm (95%-confidence interval [CI], 10.77–11.24), of the established system 8.12 mm (95%-CI, 7.84–8.42). This study revealed a significantly increased lateral as well as medial femoral rollback of knees with the innovative prosthesis design. Our intraoperative finding needs to be confirmed using fluoroscopic or radiographic three-dimensional matching under full-weight-bearing conditions after complete recovery from surgery.